s-CAPE trauma recovery program: the need for a holistic, trauma- and violence-informed domestic violence framework - Williams, Karen; Harb, Merrylord; Satyen, Lata; Davies, Mia (Frontiers in Global Women's Health, 2024)
IntroductionDomestic violence is a worldwide issue of significant concern due to its high global prevalence rates, societal costs, and the pervasive individual-level effects on physical, mental, economic, and social health and functioning. There is therefore an urgent need to deliver effective and consistent recovery services in order to mitigate the harmful societal and individual-level impacts of experiencing domestic violence and to promote victim-survivor recovery and wellbeing. This paper reviews the literature around practice models and frameworks for recovery after domestic violence and proposes the need for a holistic, trauma- and violence-informed approach to facilitate recovery and healing.FindingsResearch indicates that formal supports improve recovery and wellbeing outcomes for victim-survivors, despite some literature gaps. Trauma-and-violence-informed approaches to care and holistic support are proposed as a means of improving recovery services and minimising harm to victim-survivors while maximising wellbeing. However, the literature reveals existing service gaps, including a lack of trauma-informed services and service providers engaging in practices that are retraumatising for victim-survivors.DiscussionThe review findings indicate the lack of a clear and consistent evidence-based recovery framework to provide holistic, trauma-and-violence-informed care that is tailored to the needs of victim-survivors of domestic violence.ConclusionWe present the development of the s-CAPE trauma and recovery program, an integrated, holistic, trauma-and-violence-informed framework for recovery after domestic violence. s-CAPE was developed in Australia's first holistic, women's-only trauma treatment facility and is evidence-based and designed to address current service gaps, promoting positive recovery outcomes for victim-survivors.